Quantitative analysis and dietary risk assessment of aflatoxins in Chinese post-fermented dark tea. (December 2020) - Cui, Pu; Yan, Hangbin; Granato, Daniel; Ho, Chi-Tang; Ye, Ziling; Wang, Yong; Zhang, Liang; Zhou, Yu
Abstract: Recently, mycotoxins safety in Chinese post-fermented teas has attracted much attention because it is still controversial whether environmental fungi in the teas are able to produce aflatoxins. In this study, a rapid and selective analytical method based on immunoaffinity column (IAC) cleaning coupled with liquid chromatography-mass spectrometry (LC-MS) was developed to quantify four aflatoxins (B1, B2, G1 and G2 ) in post-fermented teas. Recoveries ranged from 80.8 to 92.2% with relative standard deviation less than 3%. The limits of detection and quantification were 0.109–0.348 μg kg −1 and 0.364–1.159 μg kg −1, respectively. Two out of 158 samples were positive for aflatoxins examination (occurrence rate 1.27%). The deterministic assessment for the maximal aflatoxins exposure under upper bound was 9.19 × 10 −6  μg kg −1 day −1 from heavy exposure consumers (≥50 year age group), but the exposure was lower than the JECFA acceptable value of 1.0 ng kg −1 day −1 on liver risk. Probabilistic assessment showed that the upper bound 95th percentile carcinogenic risk value for the 318 consumers (Yunnan China and Ulan Bator Mongolia) was 1.75 × 10 −7, and for heavy exposure consumers was 2.4 × 10 −7, and the values equally below the acceptable carcinogenic risk level. Graphical abstract: Image 1 Highlights: A rapid UPLC-Q-TOF-MS method for aflatoxins detection in tea matrix. 1.27% of dark tea samples were positive for the aflatoxins. The maximal deterministic value was 9.19 × 10 −6  μg kg −1 day −1 aflatoxins from dark teas. The 95th percentile carcinogenic risk from tea consumption is acceptable.